From (the infrequency of) war to vaccine nationalism: understanding nationalism and foreign policy in the decade of New Nationalism - Paparella, Giuseppe (National identities, 2023)
The article offers a critique of International Relations (IR) theories of nationalism and foreign policy, supplemented by an analysis of the Nationalism Studies literature on the subject. Following a discussion of the 'paradoxical status' of nationalism in IR, the article outlines a more eclectic and non-paradigmatic approach - encapsulated in the concept of 'nationalist beliefs' - that emphasises the role of cognitive psychological variables to generate a more nuanced understanding of the relationship between nationalism and foreign policy and related outcomes. The article proposes a novel conceptualisation of nationalism to better understand foreign policy in the decade of New Nationalism.